2021
DOI: 10.1186/s13561-021-00338-8
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 healthcare cost and length of hospital stay in Turkey: retrospective analysis from the first peak of the pandemic

Abstract: Background During the COVID-19 pandemic, health care systems are under extreme pressure. This study analyzed health care resource use (HCRU) and costs in patients admitted to the hospital for COVID-19 and aimed to estimate the one-year direct medical cost of the disease in Turkey. Methods This retrospective cohort study was conducted between March and July 2020 in a tertiary hospital (n = 1056) in Istanbul. Patient demographics, clinical and treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
35
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 22 publications
4
35
1
2
Order By: Relevance
“…The regression analysis shows that during this period government effectiveness is important, an indicator that has a positive influence on efficiency. Our results are similar to those obtained by [ 15 , 23 ].…”
Section: Discussionsupporting
confidence: 93%
“…The regression analysis shows that during this period government effectiveness is important, an indicator that has a positive influence on efficiency. Our results are similar to those obtained by [ 15 , 23 ].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, in hospitalized patients in Turkey, the mean LOS was 8.0 days for patients hospitalized in general wards versus 14.8 days for patients hospitalized in ICUs. This finding is consistent with our study with respect to general-wards stays and significantly less than twice the LOS in the ICU 22 .…”
Section: Discussionsupporting
confidence: 93%
“…This observation is consistent with the findings of Rae et al 12 Moreover, in hospitalized patients in Turkey, the mean LOS was 8.0 days for patients hospitalized in general wards versus 14.8 days for patients hospitalized in ICUs. This finding is consistent with our study with respect to general-wards stays and significantly less than twice the LOS in the ICU 22 . Moreover, our results found that the total ICU cost was 121,094,671.6 SAR (average cost ≈ 54,498.5 SAR), whereas the total general ward cost was 72,299,431.52 SAR (average cost ≈ 22,981.4 SAR), findings consistent with the results of a study by Khan AA et al These findings reveal that the expense of medical care increases as the severity of the patient's condition increases.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These expenses are included in the general hospitalization costs and are not influenced by the severity or outcome of the HF. Even if current literature data emphasize the high costs associated with COVID-19 hospitalization, this aspect refers mainly to cases with severe infection, with COVID-19 as the primary pathology leading to emergency admission [ 45 ]. Specifically for HF, there are intriguing data: on the one hand, the number of HF-related hospitalizations has decreased by 30–66% during pandemic period, compared to 2017–2019 [ 46 , 47 , 48 ], on the other hand, the costs per patient have increased due to severe presentations, requiring advanced supportive care and costly equipment and medication [ 47 ].…”
Section: Discussionmentioning
confidence: 99%